1991
DOI: 10.1007/bf00023422
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cDNA and genomic clones encoding 3-hydroxy-3-methylglutaryl-coenzyme A reductase from Hevea brasiliensis

Abstract: Hevea brasiliensis is the major producer of natural rubber which is cis-1,4-polyisoprene. The enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR) is involved in the biosynthesis of rubber and other plant products. We have used a hamster HMGR cDNA clone as a heterologous hybridization probe to isolate and characterize cDNA and genomic clones of HMGR from H. brasiliensis. Sequence analysis revealed that these clones fall into two different classes, HMGR1 and HMGR2. Comparison of the two classes shows 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…X54658), and HMGR3 (accession no. M74800) have been reported, [6][7][8] but the sequence information for HMGR2 was incomplete, so it was not dealth with in the current study. HMGR showed 77% identity to HMGR3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X54658), and HMGR3 (accession no. M74800) have been reported, [6][7][8] but the sequence information for HMGR2 was incomplete, so it was not dealth with in the current study. HMGR showed 77% identity to HMGR3.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Molecular biology studies have recently reported the sequences of the HMGS genes 4,5) and HMGR genes 6,7) and the sequences of the genes of the entire MVA pathway 8) in H. brasiliensis. In addition, large-scale transcriptome analyses of the latex of H. brasiliensis have been performed, 9,10) but molecular biological characterization of the MVA pathway as a whole has been inadequate.…”
mentioning
confidence: 99%
“…cDNAs and genomic HMGR clones have been isolated from Drosophila (Gertler et al, 1988), yeast (Basson et al, 1988), sea urchin (Woodward et al, 1988), hamster (Chin et al, 1984), and human (Luskey and Stevens, 1985). Recently, with the use of hamster and yeast probes plant HMGR cDNAs and genomic clones have been isolated from Arabidopsis (Caelles et al, 1989;Leamed and Fink, 1989), tomato (Narita and Gruissem, 1989;Narita et al, 1991), and Hevea (Chye et al, 1991). Sequence similarities among HMGR genes of expression of wheat (Triticum aestivum) HMGR genes because of the potential uses of their molecular components.…”
mentioning
confidence: 99%
“…MmHMGl clones could be isolated from both M. mucedo strains, whereas MmHMG2 was obtained exclusively from CBS 109. 16 Interestingly, the DNA of A. glauca gives two additional PCR bands (Fig. lA, lane 2).…”
Section: Analysis Of Pcr Fragmentsmentioning
confidence: 97%